Preliminary screening of Waltheria indica (L.) plant for its anti-inflammatory activity - Amol Chandekar,; Amber Vyas,; Neeraj Upamanyu,; Atul Tripathi,; Surendra Agrawal, (International Journal of Phytomedicine, 2017)
The investigation on anti-inflammatory activity of the various extract of Waltheria indica L. was reported to find out the pharmacological basis for its ethnomedical use. The anti-inflammatory activity of the pet ether (PEW) and methanol (MEW) extracts of the leaves of Waltheria indica L. (Malvaceae)were evaluated by using in vivo (Carrageenan & histamine induced rat paw edema, cotton pellet granuloma test) models. It was observed that, all the extracts showed significant activity in the in-vivo model at the dose of 500 mg/kg b.w. orally, when compared with control and standard drugs. Of the two extracts tested, methanol extract MEW showed most significant activity well in comparison to the standard drug. Therefore, present study suggests, potential of leaves of Waltheria indica L. in both models of acute and chronic inflammation.